(untitled) (Scientific journal of the Fergana State University, 2024)
Until today, there has not been extensive and comprehensive scientific research on the life and features of the work of Sayfiddin Mohammad Farghani - one of the greatest poets of the 13th century. In most of the tazkiras written during his lifetime and later, historiographies, as well as in the books devoted to the history of Persian and Tajik literature by domestic and foreign literary scholars, only references to Sayfiddin Mohammad Farghani are visible. In this article, some different aspects of the life and creativity of Sayfiddin Mohammad Farghani have been studied and investigated.